Dick Bierman letter to Nicholas S. Halmi regarding bird sightings, November 29, 1977 - Halmi, Nicholas S.et al (1977)
Field notes contributed by Dick Bierman in a letter to Nicholas S. Halmi. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1977. Epson - sheet feed/flatbed